Job and career satisfaction of management dietitians - Sauer, Kevin L. (Kansas State University, 2009)
Despite the enormous amount of research about job satisfaction and intent to leave, few studies have focused on Registered Dietitians (RDs) with management responsibilities. Even less is known about the level of career satisfaction or intent to leave the dietetics profession. This study examined job and career satisfaction among members of four dietetic practice groups (DPGs). An online questionnaire included 36 items of the Job Satisfaction Survey (JSS), career satisfaction and intent to leave measures. Data were analyzed from 966 dietitians in management and clinical practice using traditional statistical procedures. Management dietitians had significantly higher composite scores for six out of nine facets of job satisfaction than dietitians in non-managerial positions. Overall satisfaction scores for management dietitians (M = 153.75 ± 26.68) were also significantly higher compared to non-management dietitians (M = 140.79 ± 30.26, t = 4.368, p < 0.001). Overall satisfaction scores also differed significantly across seven groups of management dietitians, F (6, 844) = 4.41, p < 0.001. The majority of dietitians in this study did not intend to seek other jobs or leave their current jobs. Overall, management dietitians were satisfied with their careers (19.82 ± 3.73). In contrast, non-management dietitians were closer to neutral and significantly less satisfied with their careers (16.44 ± 5.06, t = 6.907, p < 0.001). Career satisfaction scores also differed significantly across seven job titles of managers, F (6, 839) = 5.69, p < 0.001. Intent to leave the profession was not observed for the majority of dietitians in this study. Additional results, implications for the dietetics profession and recommendations for future research are discussed.
Keywords: Job Satisfaction; Career Satisfaction; Operations Research (0796)